Tsunami Hazard Mapping and Loss Estimation in Yogyakarta International Airport Area - Endra Dewatama; Ikaputra (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2021)
Yogyakarta International Airport and Temon District in Regency of West Progo are located on the southern coast of Java island with the potential for tsunami disaster. The BNPB (National Agency for Disaster Relief) data along the southern coast of Java is a high priority region with high tsunami risk. This study aims to predict and analyze tsunami disasters with a height of 15 meters and 20 meters. To show the element of risk exposed using the overlay technique with a tabulated system using GIS software (Autocad and Global Mapper) to map the affected map. With a total area of study of 5,872 hectares in the 15-meter-wide scenario of the area reaching 2,836 hectares in 12 villages, the 206-hectare 206-acre scenario covers 14 villages. For the physical aspect, the 15-meter scenario is located at 6517 dilapidated buildings and the 20-meter scenario is at 9697 buildings. For the social aspect, there are 281,345 people for the 15-meter scenario and 295,554 for the 20-meter scenario. For TES Evacuation (TEA Evacuation Station) and TEA (Final Evacuation Station), for TES a total of 19 points that are TES based at Aerotropolis and TEA are on a hillside 4 kilometers from the coastline.